Modelling Changes in Bone and Body Composition Over a Season in Elite Male Footballers - Varley, Ian; Ward, Marcus; Thorpe, Chris; Beardsley, Nathan; Greeves, Julie; Sale, Craig; Saward, Chris (International Journal of Sports Medicine, 2022)
This study investigated the change in bone and body composition characteristics of elite football players and recreationally active control participants across the course of a season. Fortysix participants (20 footballers and 26 recreationally active controls) were assessed by dual-energy x-ray absorptiometry and peripheral Quantitative Computed Tomography for a range of bone and body composition characteristics at four points over the course of a competitive season. Multilevel modelling was used to examine changes. Footballers had higher characteristics than controls for 24 out of 29 dual-energy x-ray absorptiometry and peripheral Quantitative Computed Tomography variables (all p<0.05). However, there was also significant random inter-individual variation in baseline values for all variables, for both footballers and controls (p < 0.05). Wholebody bone mineral density, leg and whole-body bone mineral content, tibial bone mass and area (38%) increased across the season in footballers (p < 0.05), and there was significant random inter-individual variation in the rate of increase of leg and whole-body bone mineral content (p<0.05). Whole-body bone mineral density, leg and whole-body bone mineral content, tibial bone mass and area (38%) increased over the course of the season in elite football players. The modelling information on expected changes in bone characteristics provides practitioners with a method of identifying those with abnormal bone response to football training and match-play
Keywords: bone; exercise; football